Physical Medicine and Rehabilitation Milestone Evaluation Project: Development of Standardized Rotation-Specific Milestone-Incorporated Faculty-of-Resident Evaluation Tools. (August 2021) - Kohar, Audrey; Tran, Duc; Perret, Danielle; Chi, Bradley; Kim, Mary; Bagay, Leslie; Hata, Justin; Cuccurullo, Sara J.
Abstract : Abstract: This tri-institutional study describes the outcomes of utilization of newly developed, standardized, rotation-specific evaluations for faculty assessment of resident achievement of the physical medicine and rehabilitation milestones. Thirty-six physical medicine and rehabilitation faculty, representing three distinct academic institutions, completed a prestudy survey on the adequacy of the rotation-generic resident evaluation tools historically in use at each institution. During the 2016–2017 academic year, faculty in all three institutions consistently used a new set of rotation-specific milestone-incorporated evaluation tools. The same faculty completed surveys assessing the new evaluation tools 6 and 12 months later. Ordinal logistic regression was used to compare survey results before and after implementation of the rotation-specific milestone-incorporated evaluation tools. Results demonstrate high tool satisfaction scores, and a statistically significant improvement in the adequacy and specificity of the new evaluation tools compared with the old ones. There was also a statistically significant improvement in both faculty understanding of the milestones and faculty ability to assess the milestones with use of the new tools compared with the old ones. The implementation of standardized physical medicine and rehabilitation rotation-specific milestone-incorporated faculty-of-resident evaluation tools across three institutions improves faculty ability to assess resident overall performance specifically related to resident achievement of the milestones in each rotation. Abstract : Supplemental digital content is available in the text.